2007
DOI: 10.1002/dneu.20570
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effects on human spinal injury: Is there a basis in the in vitro studies?

Abstract: An important basis for the clinical application of small DC electric current to mammalian spinal injury is the responses of neurons in culture to applied electric fields. Our recent finding that zebrafish neurons were unresponsive to applied fields prompted us to critically examine previous results. We conclude that compelling evidence for neuronal guidance and directional stimulation of growth toward either the cathode or anode in an electric field exists only for cultured Xenopus neurons, and not for any mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
(57 reference statements)
4
28
0
Order By: Relevance
“…This finding is consistent with our previous study showing the effect of AC EFs via IDEs on hASCs (McCullen et al, 2010). The influence of DC EFs on neuronal alignment and migration has been investigated extensively (Robinson and Cormie, 2008;Yao et al, 2011). Following application of DC EFs, neurites increase their growth rate toward the cathode and degenerate, retract, and reabsorb to move away from the anode (McCaig, 1986a(McCaig, , 1986b.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is consistent with our previous study showing the effect of AC EFs via IDEs on hASCs (McCullen et al, 2010). The influence of DC EFs on neuronal alignment and migration has been investigated extensively (Robinson and Cormie, 2008;Yao et al, 2011). Following application of DC EFs, neurites increase their growth rate toward the cathode and degenerate, retract, and reabsorb to move away from the anode (McCaig, 1986a(McCaig, , 1986b.…”
Section: Discussionsupporting
confidence: 81%
“…When electric stimulation was applied to ESCs, differentiation into neuronal cell types was increased compared to the effect of growth factor application (Yamada et al, 2007). Many studies have shown that DC EFs guide neuronal growth cones in vitro (Ariza et al, 2010;McCaig 1986aMcCaig , 1986bRobinson and Cormie, 2008;Yao et al, 2011). Although less work has been done with alternating current (AC) EFs, their ability to produce asymmetric growth of neurites appears to be limited as a direct consequence of alternating the field (Ariza et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it might be possible to direct transplanted Schwann cells to appropriate regions in either the central nervous system or in peripheral nerves. Our results suggest that glial cells may be a more likely target than neurons for exogenous electrical guidance as many vertebrate neurons, especially mammalian neurons, are not sensitive to applied EFs or are inhibited in their growth, albeit sometimes asymmetrically (Robinson and Cormie, 2007).…”
mentioning
confidence: 89%
“…EFs have also been used to enhance repair of spinal cord injuries in dogs (Borgens et al, 1999) and are being used in this regard in ongoing human clinical trials (Shapiro et al, 2005). However, the target of EFs generated in those experiments is unclear as the EF magnitudes used (0.5 mV mm −1 ) were much smaller than those required to produce a directional effect on neurons in vitro, especially mammalian neurons (Robinson and Cormie, 2007). It is known that cultured neural crest cells from Xenopus and quail respond to applied EFs as small as 7 mV mm −1 by migrating toward the negative electrode (cathode) (Gruler and Nuccitelli, 1991;Stump and Robinson, 1983), so it is possible that Schwann cells may respond similarly.…”
mentioning
confidence: 99%
“…Focally applied EFs induced presumptive dendrites of embryonic rat hippocampal neurons to grow toward the cathode but had no effect on presumptive axons (Davenport and McCaig, 1993). The varying responses of neurites in culture from different organisms and preparations have led to criticism of the use of in vitro studies to guide optimization of EF-directed neuronal repair in humans (Robinson and Cormie, 2008).…”
Section: Response Of Cells To DC Electric Fields In Vitromentioning
confidence: 99%